Prior antibacterial drug exposure in dogs with meticillin‐resistant Staphylococcus pseudintermedius (MRSP) pyoderma. Issue 2 (22nd February 2016) - Hensel, Nao; Zabel, Sonja; Hensel, Patrick
Abstract : Background: The emergence of meticillin‐resistant Staphylococcus pseudintermedius (MRSP) has become a significant animal health problem. Recent studies have indicated that previous antibacterial drug exposure is a factor in acquisition of meticillin‐resistant strains of staphylococci. Hypothesis/Objectives: The purpose of this study was to identify factors associated with prior antimicrobial drug use and MRSP pyoderma in dogs presented to a veterinary teaching hospital. Animals: Dogs diagnosed with pyoderma associated with MRSP ( n = 53) or meticillin‐sensitive S. pseudintermedius (MSSP; n = 45). Methods: The medical records of dogs diagnosed with pyoderma associated with isolation of S. pseudintermedius between January 2006 and November 2012 were reviewed. All cases with a complete twelve month to 3 yr drug history prior to the diagnosis were included. Results: Fifty two of 53 (98%) MRSP cases and 42 of 45 (93%) MSSP cases had received at least one course of antibacterial drug prior to diagnosis. The total number of antibacterial drug prescriptions provided to pet owners and the variety of antibacterial drug classes represented were higher for cases with MRSP than for cases with MSSP ( P < 0.0001 and P = 0.009, respectively). More cases with MRSP (98%) received beta‐lactam drugs than those with MSSP (82%; P = 0.007) and the proportion of MRSP cases that had received concurrent immunomodulatory therapy was higher (62% versus 42%; P = 0.048). Conclusions and clinical importance: These results suggest that the total number of antibacterial drug prescriptions, exposure to multiple drug classes (beta‐lactams in particular) and concurrent immunomodulatory therapy may be associated with increased risk for acquisition of MRSP. Abstract : Background – The emergence of meticillin‐resistant Staphylococcus pseudintermedius (MRSP) has become a significant animal health problem. Recent studies have indicated that previous antibacterial drug exposure is a factor in acquisition of meticillin‐resistant strains of staphylococci.Hypothesis/Objectives – The purpose of this study was to identify factors associated with prior antimicrobial drug use and MRSP pyoderma in dogs presented to a veterinary teaching hospital.Conclusions and clinical importance – These results suggest that the total number of antibacterial drug prescriptions, exposure to multiple drug classes (beta‐lactams in particular) and concurrent immunomodulatory therapy may be associated with increased risk for acquisition of MRSP.